Elevated temperature, freezing-thawing and wetting-drying effects on polypropylene fiber reinforced metakaolin based geopolymer composites - Aygormez, Yurdakul; Canpolat, Orhan; Al-mashhadani, Mukhallad M.; Uysal, Mucteba (ELSEVIER SCI LTD, 2020)
In this study, metakaolin-based geopolymer samples produced by substitution of silica fume and cole-manite waste up to 20% were subjected to high-temperature effects at 300, 600, 900 degrees C, the wetting-drying effect of 5, 15 and 25 cycles and freezing-thawing effect of 56 and 300 cycles. At the end of the tests, compressive and flexural strengths, ultrasonic pulse velocity and weight changes' results were examined. In addition to these, micro-computed tomography (CT), XRD and SEM analyses were performed to examine the microstructure properties as well as visual inspection. 5 series produced for high temperature and wetting-drying effects were also produced with polypropylene fiber. It has been observed that samples exposed to 900 degrees C maintained their stability. Polypropylene fiber has been shown to increase the samples' flexural strength results compared to the non-fiber samples after exposing to high temperatures. For the freezing-thawing effect, air-entraining admixture was added to 5 series. An increase for compressive strength was seen after 56 cycles but a decrease was seen after 300 cycles. The geopolymer samples thus began to suffer the real distortion effect in subsequent cycles after the freezing-thawing effect, which contributed to geopolimerization in a sense occurring in the first 56 cycles. During the wetting-drying cycles, fluctuations were observed in the results and an increase in the compressive strength, UPV and weight changes' results after 5 cycles, a decrease in the results after 15 cycles and an increase again in the results after 25 cycles were seen. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer; Metakaolin; Silica fume; Colemanite waste; High temperature; Freezing-thawing; Wetting-drying; Polypropylene fiber; Air entraining admixture; F FLY-ASH; CEMENT-BASED COMPOSITES; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; THERMAL-BEHAVIOR; LONG-TERM; PORTLAND-CEMENT; HEAT-TREATMENT; Construction & Building Technology; Engineering; Materials Science